Game theory based trust management method for mobile ad hoc networks - Jing-jing GUO; Jian-feng MA; Qi LI; Tao WAN; Cong GAO; Liang ZHANG (Tongxin xuebao)
A game model is proposed for the indirect trust information obtaining process.A suitable punishment mechanism and design the utility function for nodes in a MANET is given.Moreover，with evolutionary game theory，the trust evolution of nodes using replicator dynamic equation is analyzed and several theorems toillustrate preconditions under which each evolutionarily stable strategy can be achieved are proposed.Experiments verified the correctness and effectiveness of proposed method and simulated the dynamic evolutionary trend of the nodes under different parameters which experimentally proves the proposed theorems.